The G20 Leaders and global governance - Ngaire Woods (University of Oxford, Global Economic Governance Programme (GEG), 2010)
This paper presents a short, analytical history of the G20 Leaders group. It examines the impact of the G20 on outcomes in international cooperation, and its impact on processes and institutions of global governance. The first part of the paper traces the trajectory of the G20 across its first four meetings, highlighting that after the initial "crisis committee" phase of the G20, the cooperation achieved by the grouping waned dramatically. The second part of the paper examines whether the global agenda has been broadened or influenced by the inclusion of emerging economies. The third and final part of the paper examines the prospects for the G20 looking forward, sketching out four major areas in which the G20 needs to act as an agenda-setter and orchestrator of global governance. To foreshadow the conclusions, the G20 is uniquely placed as an informal agenda-setting group, to push forward global cooperation in four key areas: financial regulation, development assistance, exchange rates, and international institutional reform.
Keywords: 330; Global Governance; Führungskräfte; G20-Staaten